2014
DOI: 10.1021/je5000764
|View full text |Cite
|
Sign up to set email alerts
|

Use of Equations of State and Coarse Grained Simulations to Complement Experiments: Describing the Interfacial Properties of Carbon Dioxide + Decane and Carbon Dioxide + Eicosane Mixtures

Abstract: We report surface tension measurements, coexisting densities, concentration profiles along the interfacial region, surface activities, and relative Gibbs adsorption isotherms for binary mixtures of carbon dioxide (CO 2 ) + n-decane (n-C 10 H 22 ) at 344.15 K and carbon dioxide (CO 2 ) + n-eicosane (n-C 20 H 42 ) at 323.15 K over a pressure range from 0.1 MPa to 10.35 MPa. The results are obtained by employing a broad approach that integrates experiments with both theory and molecular simulations to gain an enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 80 publications
15
111
0
Order By: Relevance
“…However, possibly, the most interesting feature of these equations is the direct and quantitative link to the underlying potential, such that information gathered experiments can be incorporated into intermolecular potentials of interest here, is to garner experience from the molecular simulation of vapor-liquid interfaces to directly feed into this framework, in order to build a robust and transferable model capable of predicting the properties of an interfacial system from a minimal amount of commonly available experimental information, such as critical constants (see Refs. [65][66][67][81][82][83][84][85][86][87] for a complete discussion).…”
Section: -21mentioning
confidence: 99%
“…However, possibly, the most interesting feature of these equations is the direct and quantitative link to the underlying potential, such that information gathered experiments can be incorporated into intermolecular potentials of interest here, is to garner experience from the molecular simulation of vapor-liquid interfaces to directly feed into this framework, in order to build a robust and transferable model capable of predicting the properties of an interfacial system from a minimal amount of commonly available experimental information, such as critical constants (see Refs. [65][66][67][81][82][83][84][85][86][87] for a complete discussion).…”
Section: -21mentioning
confidence: 99%
“…45,46 In this work we modeled THF as a single-and double-segment pearl-necklace model, without any additional electrostatic interactions, estimated from the corresponding states principle (or critical data) proposed by Mejía et al 41 This methodology has shown great flexibility to characterize vapor-liquid interfacial properties of pure fluids 47 and complex mixtures of dilute surfactant solutions 48 and natural gases and condensates. 47,[49][50][51] Table I summarizes the SAFT parameters for THF as used in molecular simulations in this work. Nevertheless, the methodology proposed by Mejía et al 41 cannot be used directly in a rigid configuration, because energy contribution in Eq.…”
Section: A Saft-coarse Grained Mie Force Fieldmentioning
confidence: 99%
“…Invoking the SGT, the interfacial tension of a binary mixture, γ, is given by the following integral expression: [23][24][25][26][27][28][29][30][31][32][33][34][35]66,67]…”
Section: Square Gradient Theory For Modeling Of Phase Equilibrium Andmentioning
confidence: 99%
“…On the other hand, theoretical descriptions of these mixtures have been made by employing Density Functional Theory (DFT) [13,14,22], Density Gradient Theory (DGT) or Square Gradient Theory (SGT) [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. Furthermore, molecular simulations based either on Molecular Dynamics or Monte Carlo schemes have also been employed [19,30,31,39,40,41] to garner information on the interfacial properties of these systems. An analysis of the above mentioned references reveals that there are key points that must be taken into account: First, an unequivocal full description of interfacial properties requires -at least-two independent approaches, as some previous works have demonstrated (see for instance and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation